Maxizyme-mediated specific inhibition on mutant-type p53 in vitro - Kong, Xin-Juan (World J Gastroenterol, 2003)
AIM: To evaluate the specific inhibition of maxizyme directing against mutant-type p53 gene (mtp53) at codon 249 in exon 7 (AGG→AGT) in vitro. METHODS: Two different monomers of anti-mtp53 maxizyme (maxizyme right MzR, maxizyme left MzL) and control mutant maxizyme (G(5)→A(5)) were designed by computer and cloned into vector pBSKU6 (pBSKU6MzR, pBSKU6MzL). After being sequenced, the restrictive endonuclease site in pBSKU6MzR was changed by PCR and then U6MzR was inserted into pBSKU6MzL, the recombinant vector was named pU6Mz and pU6asMz (mutant maxizyme). Mtp53 and wild-type p53 (wtp53) gene fragments were cloned into pGEM-T vector under the T7 promoter control. The (32)p-labeled mtp53 transcript was the target mRNA. Cold maxizyme transcripts were incubated with (32)p-labeled target RNA in vitro and radioautographed after denaturing polyacrylamide gel electrophoresis. RESULTS: In cell-free systems, pU6Mz showed a specific cleavage activity against target mRNA at 37 °C and 25 mM MgCL(2). The cleavage efficiency of pU6Mz was 42%, while pU6asMz had no inhibitory effect. Wtp53 was not cleaved by pU6Mz either. CONCLUSION: pU6Mz had a specific catalytic activity against mtp53 in cell-free system. These lay a good fundation for studying the effects of anti-mtp53 maxizyme in HCC cell lines. The results suggest that maxizyme may be a promising alternative approach for treating hepatocellular carcinoma containing mtp53.